Easy Access to Quinolin-2(1H)-ones via a One-Pot Tandem Oxa-Michael–Aldol Sequence - Jarrige, Lucie; Merad, Jeremy; Zaied, Siwar; Blanchard, Florent; Masson, Géraldine (Synlett, 2017)
An efficient strategy for the synthesis of a variety of quinolin-2(1H)-one derivatives has been developed. The reaction proceeded from cinnamide derivatives via a tandem reaction in the presence of NaOH to afford the corresponding 2- quinolin-2(1H)-one derivatives in good to excellent yields.
Keywords: quinolinone; tandem process; heterocycles; Michael addition; intramolecular aldol reaction